Polymer assist crystallization and passivation for enhancements of open-circuit voltage and stability in tin-halide perovskite solar cells. (8th October 2018) - Deng, Liangliang; Wang, Kai; Yang, Hanjun; Yu, Haomiao; Hu, Bin
Abstract: It has been a widely-known and intractable issue due to very rapid degradation of tin (Sn) based organic-inorganic hybrid perovskites (OIHPs). To incorporate organic chain polymers into the OIHPs based photo-active polycrystalline films seems to be a unique strategy to passivate naturally formed defects at grain boundaries and surfaces, to prevent surface oxidation, and consequently, to optimize photovoltaic performance, as well as to tackle with device instability. In this work, a Lewis-type organic insulating polymer, polymethylmethacrylate (PMMA), was utilized as an effective additive in formamidinium tin tri-iodide (FASnI3 ) precursor solutions, and the corresponding solid films were made by a one-step processing method. By tuning different concentrations of PMMA, the solar cells have exhibited remarkable improvements of and FF by comparing with a control device without PMMA. The role of PMMA is functional for surface morphology optimization, trap density reduction and current density–voltage ( J–V ) hysteresis elimination. As a result, it is helpful to effectively impede degradation speeds of FASnI3 based solar cells.